Assessing the Perceived Impacts of Community Participation on Rural Development Effectiveness: An Empirical Study of Langchenphu Gewog, Bhutan - Wangdi, Dorji (Advances in Social Sciences Research Journal, 2026)
Bhutan's democratic decentralization has made community participation an essential element of rural development, empowering grassroots citizens to self-manage their social, economic, and environmental well-being. Nevertheless, in practice, the level of community participation in rural development programs and citizens' perceptions of their contribution, remain unknown. Hence, this study assesses the perceived impact of community participation on rural development effectiveness. This study employed a household census survey, covering every household in Langchenphu Gewog (Block). Data were collected from 237 respondents, consisting of household heads or any eligible member of the household whose age is 18 and above. Information was gathered using a structured, closed-ended Likert-scale questionnaire. Information was gathered using structured, closed-ended Likert-scale questionnaires. The community participation levels was measured using six key indicators, and the perception of the effectiveness of rural development was assessed using three dimensions, which were quantified through nine specific indicators. Descriptive statistics, correlation analysis, and multiple linear regression were applied to the quantitative data. Results indicated a strong positive correlation between perceived community participation and the effectiveness of rural development (r = 0.839, p < .001; β = 0.831). In addition, multiple regression analysis revealed that participation was a strong predictor of project success outcomes, while demographic factors did not have any significant impact. These findings confirm that inclusive and wide-ranging participation is more decisive than demographically specific intervention. Therefore, the study recommends the institutionalization of participatory practices, the development of community capacity, and the strengthening of local governance bodies' accountability for effective and inclusive rural development.